1997
DOI: 10.1037/0096-1523.23.4.962
|View full text |Cite
|
Sign up to set email alerts
|

Age and IQ effects on stimulus and response timing.

Abstract: Normal older participants (aged 60-79 years), with known scores on the Culture Fair Intelligence Test, were tested on 4 timing tasks (i.e., temporal generalization, bisection, differential threshold, and interval production). The data were related to the theoretical framework of scalar timing theory and ideas about information processing and aging. In general, increasing age and decreasing IQ tended to be associated with increasing variability of judgments of duration, although in all groups events could be ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
108
5
5

Year Published

2001
2001
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(139 citation statements)
references
References 45 publications
(91 reference statements)
21
108
5
5
Order By: Relevance
“…Additionally, research on aging has shown that the elderly do not show biases relative to younger individuals in their performance on the bisection task, even if the elderly are more variable in their responses (McCormack, Brown, & Maylor, 1999;Wearden, Wearden, & Rabbitt, 1997).…”
Section: Accepted Manuscript Embodying Effects 13mentioning
confidence: 99%
“…Additionally, research on aging has shown that the elderly do not show biases relative to younger individuals in their performance on the bisection task, even if the elderly are more variable in their responses (McCormack, Brown, & Maylor, 1999;Wearden, Wearden, & Rabbitt, 1997).…”
Section: Accepted Manuscript Embodying Effects 13mentioning
confidence: 99%
“…Other studies, however, use large groups of participants and collect less data from each participant. In this case, authors usually draw inferences from pooling the data across participants (e.g., Ono & Kitazawa, 2009;Ortega & López, 2008;Wearden, Wearden, & Rabbitt, 1997). Data analysis is then performed on the aggregated data set, which is statistically more stable than each individual data set.…”
Section: Analysis Of Aggregated Datamentioning
confidence: 99%
“…Third, responses at test are based on the outcome of decision processes that compare representations of the reference durations with just-presented test durations. These processes are typically captured mathematically in scalar timing models (e.g., McCormack et al, 1999;Wearden, 1991Wearden, , 1999Wearden, Wearden, & Rabbitt, 1997). A key advantage of carrying out developmental studies of timing within the Scalar Expectancy Theory framework is that such formal models enable developmental changes to be pinpointed in particular components of the processing stages.…”
Section: Introductionmentioning
confidence: 99%